Prevalência de enteropatógenos em suínos de recria/terminação em Minas Gerais e desenvolvimento de modelo experimental murino de enteropatia proliferativa - Aline de Marco Viott (2010)
The prevalence of Lawsonia intracellularis, Brachyspira pilosicoli, Brachyspira hyodysenteriae, Salmonella spp., enterotoxigenic E. coli, Trichuris suis and the occurrence of mixed infections was investigated, as well as the susceptibility of four different mice strains (Swiss, BALB / c, C-57 BLACK 6 and DB-A) to L. intracellularis infection. Forty-six herds were selected in the four main swine production regions in the state of Minas Gerais. The overall herd prevalence of L. intracellularis, Salmonella enterica serotype Typhimurium and enterotoxigenic E. coli were 19,56%, 6,52%, 10,87% respectively. Mixed infection was diagnosed in 30,43% of herds, and L. intracellularis and Salmonella enterica serotype Typhimurium are the main pathogens association (10,87%). Brachyspira pilosicoli was diagnosed only in two herds, always associated with mixed infections. B. hyodysenteriae and Trichuris suis were not identified in any samples analyzed. One hundred sixty mice (n = 40 per strain) were intragastrically inoculated with pure culture or mucosa homogenate containing L. intracellularis. Two DB-A mice exhibited gross lesions at 14 days after inoculation. All mice strains studied showed histological lesions of proliferative enteropathy and positive IHC, varying according to the intensity of the lesion. The most severe lesions were observed in DB-A and Swiss mice inoculated with pure culture. The elimination in feces of L. intracellularis was observed, by Nested PCR, in all lines with some variations.